Politik Kewarganegaraan Masyarakat Kelurahan Kisaran Naga (Studi Kasus Pada Pemilihan Calon Anggota DPRD Kabupaten Asahan Tahun 2019) - Juli Natalia Silalahi (Universitas Muhammadiyah Makassar, 2020)
The purpose of this study was to analyze the politics of citizenship (liberal or democratic) in the Kisaran Naga Village Society in the context of the Election of Prospective Members of the Asahan Regency DPRD in 2019. This study used a qualitative research method with a case study approach to the citizenship politics in the community of Kisaran Naga, Kota Kisaran Timur District , Asahan Regency. Data collection techniques through observation, in-depth interviews and secondary data collection. Data validity uses multiple sources of evidence from expert informants, ordinary informants, and secondary data. Data analysis with an interactive model that is data reduction, data presentation, and drawing conclusions.The results of this study are contextual that occurs in citizens in the village of Kisaran Naga in understanding the legislative elections of Asahan Regency in Electoral District 1 is still a liberal citizenship. That is, citizens still understand the legislative election as a capitalist movement (money politics), identity political movement (religion, ethnicity (clan)) so that the condition affects the understanding of citizens not to give too much concern to the running of democratic legislative elections. The movement to reject money politics as the basis of the capitalist movement is evident in 1 subject of informants, but the condition still falls on the choice of citizens who choose candidates based on identity politics. So, liberal citizenship is still quite strong in the tradition of citizens in the Kisaran Naga Village.